Itraconazole Reverts ABCB1-Mediated Docetaxel Resistance in Prostate Cancer - Lima, Thiago S.; Souza, Luciano O.; Iglesias-Gato, Diego; Elversang, Johanna; Jørgensen, Flemming Steen; Kallunki, Tuula; Røder, Martin A.; Brasso, Klaus; Moreira, José M.A. (Frontiers in Pharmacology, 2022)
Docetaxel (DTX) was the first chemotherapeutic agent to demonstrate significant efficacy in the treatment of men with metastatic castration-resistant prostate cancer. However, response to DTX is generally short-lived, and relapse eventually occurs due to emergence of drug-resistance. We previously established two DTX-resistant prostate cancer cell lines, LNCaPR and C4-2BR, derived from the androgen‐dependent LNCaP cell line, and from the LNCaP lineage-derived androgen-independent C4-2B sub-line, respectively. Using an unbiased drug screen, we identify itraconazole (ITZ), an oral antifungal drug, as a compound that can efficiently re-sensitize drug-resistant LNCaPR and C4-2BR prostate cancer cells to DTX treatment. ITZ can re-sensitize multiple DTX-resistant cell models, not only in prostate cancer derived cells, such as PC-3 and DU145, but also in docetaxel-resistant breast cancer cells. This effect is dependent on expression of ATP-binding cassette (ABC) transporter protein ABCB1, also known as P-glycoprotein (P-gp). Molecular modeling of ITZ bound to ABCB1, indicates that ITZ binds tightly to the inward-facing form of ABCB1 thereby inhibiting the transport of DTX. Our results suggest that ITZ may provide a feasible approach to re-sensitization of DTX resistant cells, which would add to the life-prolonging effects of DTX in men with metastatic castration-resistant prostate cancer.